A BIBLIOGRAPHY ON WINTER CONSTRUCTION 1940 - 1963 - Fulwider, Charles W. (1965)
The references contained in this bibliography were derived primarily from a search of the U. S. Army Cold Regions Research and Engineering Laboratory library, the Arctic Bibliography, the Bibliography on Snow, Ice and Permafrost (USA CRREL Report No. 12, Volumes 1-18), the Polar Bibliography, the Industrial Arts Index and the Applied Science and Technology Index. The period covered by the bibliography purposely was limited to the years 1940-1963 because of the rapid technological advances since World War II, which in many cases have resulted in complete changes in construction procedures and practices. Each item has been numbered to dispense with repetition of listings containing information on several subjects. Additional references under a particular subject are shown by number at the end of the subject listing. The Arctic Bibliography and the Bibliography on Snow, Ice and Permafrost supplied a large number of the references. Both publications number and provide abstracts for each item. Each reference in this report obtained from these two sources has the abstract number noted below the listing for those desiring additional information. (Author)